TEOLOGI WAHABI: SEJARAH, PEMIKIRAN DAN PERKEMBANGANNYA - Unggul Purnomo Aji; Kerwanto (LPPM STAI Nida El-Adabi, 2023)
Wahabi’s school of thought was pioneered by Muhammad ibn Abdul Wahab’s thought who was indirectly inspired by Ibn Taimiyyah’s spirit of renewal in the context of purifying the faith. In its existence, this school has emerged and developed inseparable by the support from Saud family on symbiosis mutualism behind it. Paradigmatically, this school has a tendency not to adhere to any schools in fiqh and tasawwuf, but in its faith, it adopts the concept of Ibn Taymiyyah’s trilogy of aqidah, namely: Rububiyah, Uluhiyah, and Asma wa Sifat. Dialectically, it’s a puritanist, literalist, revivalist, and tends to be rigid in practice. This thought has a blur limit of worshiping which consequently has a tendency of being takfiri. Consequently, it cannot be separated from its pros and cons in its journey even when they have changed their way of spreading to be more diplomatic nowadays.